Effect of progressive deinking and reprinting on inkjet-printed paper - SÖNMEZ, SİNAN (My University, 2022)
The main aim of the present research is to examine the effect of progressive deinking and reprinting on the paper properties of inkjet-printed paper. A typical office copy paper was selected as the base paper and printed using an inkjet printer having at least 50 % ink coverage. Thereafter, it was deinked and reprinted thrice, and its paper properties were measured. The paper properties that were measured were roughness, porosity, opacity, brightness, specular gloss, whiteness, bursting strength, tearing resistance, tensile strength, contact angle, deinkability efficiency, visible dirt area, ink elimination factors, and color differences. The results showed that in comparison to the base paper, the progressively deinked and reprinted paper samples showed an increase in roughness, porosity, opacity, tearing resistance, dirt area, and color difference. On the other hand, there was a decrease in brightness, gloss, whiteness, burst strength, tensile strength, contact angle, deinkability efficiency, and ink elimination factors. The experiment shows that the progressively deinked and reprinted papers can be compared to the base paper in the major paper properties.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KAĞIT & AHŞAP; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, PAPER & WOOD; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; deinking; inkjet; paper; printability; recycling; PULP FIBERS; ROUGHNESS; PROSPECTS; STRENGTH; QUALITY; LIGNIN; MEDIA; INKS